Assessment of Occupational Stress in Medical Doctors Working in Tertiary Care Hospital - Dipika Baria1 , Tejas J. Shah2, Shruti Brahmbhatt3 , Mahavir Rajput4 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Nowadays, stress has commonly been assessed especially in medical doctors. The reason forthe same is that medical doctors have to play high competitive roles and in turn have so many responsibilitieskeeping in mind the holistic care to patients.Aim/objective: To assess occupational stress in medical doctors working in tertiary care hospital ofBhavnagar, Gujarat.Materials and Methods: This cross-sectional study was conducted during September 2017 to December2017 after prior approval of institutional ethics committee. Total 75, both male and female medical doctorswere enrolled as study participants after written informed consent and based on inclusion criteria. Along withcase record performa, self-administered pre-tested questionnaires having stress scale namely ProfessionalStress Scale (PSS) and Perceived Stress Scale 10 items (PSS-10) were given to all participants as a studytool. The data of scores received on scales was and entered in Microsoft excel and the same was analyzedby using GraphPad Prism 5 software for various proportions, associations and frequencies. The associationswere considered significant if the p value is less than 0.05.Results: Out of 75, total 50 participants filled and submitted the questionnaires. The mean age of participantswas 31.96 years. As per the stress scales used, moderate stress was observed among medical doctorsirrespective of sex. The commonest symptom observed among stressed doctors was sleep disturbances(insomnia).Conclusion: Moderate to mild stress was found among medical doctors. Stress in medical doctors is neverunderestimated irrespective of sex. Insomnia is the commonest symptom observed among stressed doctors.